Сучасні підходи, тенденції та інновації в управлінні персоналом аграрних підприємств - Лещенко, Зиновія Богданівна; Липовий, Дмитро Валерійович; Гарбажій, Катерина Станіславівна (Національний технічний університет "Харківський політехнічний інститут", 2024)
У статті представлено результати дослідження щодо визначення сучасних підходів, тенденцій та інновацій в управлінні персоналом, які можуть бути запроваджені в практичну діяльність українських аграрних підприємств. Доведено, що успіх в діяльності будь–якого підприємства в першу чергу залежить від наявності дієвої системи управління персоналом. Встановлено, що традиційне управління персоналом більше орієнтоване на виконання адміністративних функцій, тоді як сучасний HR-менеджмент відіграє стратегічну роль на підприємстві, спрямовану на розвиток співробітників і створення ефективного та залученого робочого середовища. Визначено, що належне сучасне управління персоналом потребує інноваційних методів, серед яких: персоналізовані програми мотивації, застосування аналітики для прийняття рішень, робота в командах на основі проектів тощо. Наголошено на важливості орієнтування керівників і кадровиків на більш широке застосування в практичній кадровій роботі digital-технологій.

Most enterprises face the fact that existing approaches to personnel management only sometimes bring significant results. Therefore, a modern approach to working with personnel is necessary.The tasks of any enterprise's personnel service should be broader than personnel accounting, document management, monitoring compliance with established rules, etc. The main thing is developing employees and forming a successfully functioning team — the collective of an agrarian enterprise.The article's purpose is to identify modern approaches, trends, and innovations in personnel management that can be implemented in the practical activities of Ukrainian agricultural enterprises. The article presents the results of research on the definition of modern approaches, trends, and innovations in personnel management that can be introduced into the practical activities of Ukrainian agricultural enterprises. It has been proven that the success of any enterprise primarily depends on the availability of an effective personnel management system. It was determined that proper modern personnel management requires innovative methods, including: personalized motivation programs, application of analytics for decision-making, work in project-based teams, etc. It's crucial to underscore the importance of equipping managers and HR personnel with the skills to effectively utilize digital technologies in their practical personnel work.
Modern approaches, trends and innovations in personnel management of agricultural enterprises
Keywords: управління персоналом; аграрні підприємства; аграрний менеджмент; інноваційні методи; програми мотивації; кадрова робота; agricultural enterprise; personnel development; innovative methods; agricultural management